Pembuatan Stiker sebagai Penanaman Edupreneurship pada Anak Sekolah Dasar Kelas Dua - Addini, Faoziah Nur (Pena Edukasia, 2023)
This article discusses the activity of making stickers to cultivate edupreneurship in second grade elementary school student. The method used is literature study. The discussion covers processes need to be carried out in carrying out sticker making activities such as planning, implementation, monitoring, evaluating, and continuation planning of this activities.